Political connections and cost of debt: evidence from China - Ying, Pan (2017)
With the development of the Chinese economic market and Chinese economic transactions, firms are full of enthusiasm about building relationships with government officials. Under such a background, political connections are becoming important issues. Seeking good political ties, as attested by many empirical studies, proved that political connections have relationships with the firm’s tax, donation, capital structure and so on. However, the objective of this study was to examine the relationship between political connections and the cost of debt, which is crucial for firms to develop because the main financial institutions are controlled by the government in China. In this study, the political connections issue revolved around the cost of debt in 100 Chinese firms which were listed in the Shenzhen stock exchange in 2015. In addition, this study extended previous studies through an empirical study to examine the relationships between political connections and the cost of debt in China. A very interesting and new part in the research was introducing a new measurement of political connections. Besides using Faccio, Lang, and Young's (2001) dummy variable as the measurement, this study also tested the political connections from the Chinese national hierarchy positions. After using this new measurement, the result became more accurate and appropriate to Chinese social conditions. The result of this study shows that political connections and the cost of debt in China are significant and negative, which means in current China, firms are eager to request the government to be their patron. Therefore, the Chief Executive Officer (CEO) or the board of directors (BOD) are willing to wear two hats—one is to carry the burden in the firm, and the is holding a position with political attributes. Moreover, this study enriches previous studies and makes contributions to this field. As the data and the duration are small, there are limitations to this study which provide a direction for future study.